Photomechanical Azopolymers and Digital Polarization Optics: A Versatile Platform for Surface Microstructure Fabrication - Strobelt, Jonas; Santer, Svetlana; Abourahma, Heba; Music, Mika; Farzan, Zay; Nezamis, Phillip; Leon, Ryan; McGee, David J. (ACS applied optical materials, 2025)
The photomechanical response of azobenzene-polymer films to polarized light is sufficiently strong to drive micron-scale surface relief formation. With a multitude of photonics applications, such optically written microstructures have motivated research to identify azopolymers and optical polarization technologies best matched to translate this phenomenon to practical devices. Here we present an overview of this field, with focus on a promising laser-writing platform based on structured polarized light projection from a high-resolution spatial light modulator. This photofabrication approach can print static and dynamic surface microstructures. It is also maskless and single-beam, writing structures with 600 nm feature size and >1 μm amplitude in real-time. The printed structures require no wet-chemical processing and are available for replication immediately after exposure. We also present a new application in color synthesis by printing surface gratings that collinearly diffract red, green, and blue light, demonstrating the potential of this approach in the field of structured color.